A “Feeling-Thinking” School for the Recognition and Practice of Human Rights - Espinosa Gómez, Deyby Rodrigo (Rastros Rostros, 2014)
The fundamental aim of this article is to identify other possible transformative actions for rethinking schools in the 21st century. This involves changing the concept of schools from institutions that teach and reproduce what has already been thought, and that regulate and orient students to educate themselves according to what they should do in relation to competencies, work and the company, to places that focus on what individual students want to do in a world that increasingly demands more education to recognize and practice human rights through a “feeling-thinking process”, that is, a process determined by both heart and mind. This reflection is underpinned by the fields of critical pedagogy, popular education, open schooling, human rights education, and the critical stance of the curriculum. The research that gave rise to this article was titled “Teachers on the Move for Human Dignity: A Strategy for Recognizing and Practicing Human Rights for a Citizen School and a Critical Curriculum”, which was conducted in 2012 and 2013 at Universidad de Antioquia, and carried out with students at the Pedro de Castro school in the city of Medellin. Its aim was to build an educational strategy with these students involvingthe recognition and practice of human rights for a citizen school and a critical curriculum, based on the principle of dialog between students and teachers, and in the spirit of later taking this teaching to the general community
Keywords: community; emancipating curriculum; human rights; “feeling-thinking” school; teacher